1985
DOI: 10.1038/ki.1985.76
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous glomerular IgA deposition in ddY mice: An animal model of IgA nephritis

Abstract: It was found that ddY mice derived from non-inbred dd-stock mice brought from Germany before 1920 and then raised in Japan developed spontaneously IgA dominant deposition in the glomerular mesangium. In this report we give a detailed natural history of the renal pathology of those mice. The animals were fed rodent laboratory chow and sacrificed in groups of 9 to 10 at 6, 10, 16, 24, 28, 40, and 59 weeks of age. The bladder urine was analyzed, serum immunoglobulins were measured, and the kidney specimens were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
95
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(99 citation statements)
references
References 10 publications
4
95
0
Order By: Relevance
“…The other was the ddY Norm mice population with the IgA level within the mean 72 s.d.s of BALB/c mice throughout the whole course of the experiment. This result was consistent with the genetic segregation analysis observed in the closed-colony ddY population carried out by Imai et al 8 Next, we studied the age-dependent changes of urinary IgA concentration in ddY mice. Although we could also observe the elevation of IgA in urine among ddY High mice to some extent, the magnitude of age-dependent IgA increase in urine was very low.…”
Section: Age-dependent Changes Of Serum and Urinary Iga Levelssupporting
confidence: 77%
See 1 more Smart Citation
“…The other was the ddY Norm mice population with the IgA level within the mean 72 s.d.s of BALB/c mice throughout the whole course of the experiment. This result was consistent with the genetic segregation analysis observed in the closed-colony ddY population carried out by Imai et al 8 Next, we studied the age-dependent changes of urinary IgA concentration in ddY mice. Although we could also observe the elevation of IgA in urine among ddY High mice to some extent, the magnitude of age-dependent IgA increase in urine was very low.…”
Section: Age-dependent Changes Of Serum and Urinary Iga Levelssupporting
confidence: 77%
“…8 We found that we could classify ddY mice into at least two subgroups. One was a HIGA group that exhibited some symptoms of IgAN through aging (ddY High ), and the other was a normal serum IgA group without IgAN (ddY Norm ).…”
mentioning
confidence: 97%
“…23 Indeed, among the murine models of IgAN, those with hematuria and glomerular dysfunction are typically the ones with mesangial complement deposition; [23][24][25][26] conversely, those without complement generally have normal glomerular function. [27][28][29] However, in the system described herein, a pathogenic role for the complement system is improbable, since hematuria occurred even in mice with little or no glomerular C3 deposits.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies suggest a significant difference in the incidence/prevalence among different ethnic groups and support significant familial aggregation (6). Data from mouse studies, including the outbred strain ddY (8) and knockout and transgenic approaches (9 -11), have shown that specific genetic alterations in a model organism give rise to a phenotype that shares features with the human disease.…”
mentioning
confidence: 99%